Burnout Among School Teachers During the COVID-19 Pandemic in Jazan Region, Saudi Arabia - Alqassim, Ahmad Y.; Shami, Mohammed O.; Ageeli, Ahmed A.; Ageeli, Mohssen H.; Doweri, Abrar A.; Melaisi, Zakaria I.; Wafi, Ahmed M.; Muaddi, Mohammed A.; El-Setouhy, Maged (Frontiers in Psychology, 2022)
Background. Burnout is a syndrome that results from stressors in the work environment that have not been successfully managed. The prevalence of burnout among schoolteachers was always controversial. COVID-19 pandemic added more stressors to teachers since they had to change their working styles in response to the pandemic lockdowns or curfews. In Saudi Arabia, the prevalence and determinants of burnout among school teachers were not measured by any other group during the COVID-19 pandemic stressors. Methods. A cross-sectional survey was conducted among 879 teachers in the Jazan region, Saudi Arabia, using the Maslach Burnout Inventory (MBI), during April 2021. Multistage cluster random sampling was used. Results. The mean age of the participants was 41.4(+ 6.9) years. Male teachers represented 52.6% of the participants while females represented 47.4%. Most teachers showed burnout symptoms (69.6%). Consequences of burnout were observed, such as using psychotropic medications (4.6%), absenteeism (45.6%), lack of job satisfaction (7.7%), and changing schools (15.8%). Using the MBI scale, most teachers showed medium or high emotional exhaustion (57.6%), low depersonalization (62.2%), and low personal accomplishment (51.4%). Conclusion. Most teachers showed symptoms of burnout during the COVID-19 pandemic. Being an expert and ability to adapt to technology during the COVID-19 pandemic proved to effectively reduce burnout symptoms. Increasing incentives, early detection, and improving the work environment is recommended to diminish burnout consequences.